2018
DOI: 10.1089/dia.2018.0157
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Point-of-Care Equipment for Glucose Measurement in Screening for Dysglycemia in Patients with Coronary Artery Disease

Abstract: The HemoCue point-of-care system is accurate for dysglycemia screening in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 147 publications
(186 reference statements)
0
5
1
Order By: Relevance
“…Furthermore, it has the advantage of providing a diagnosis immediately so that treatment can start promptly. In previous comparisons with laboratory glucose measurements, the HemoCue Glucose 201 system has been found to be accurate [27,28]. When HC210RT was compared to accredited hospital laboratory methods in subjects with coronary artery disease in a European survey, the Bland-Altman plot showed small differences and, in contrast to our findings, a tendency of higher glucose measurements for HC201RT than for hospital laboratory measurements [28].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, it has the advantage of providing a diagnosis immediately so that treatment can start promptly. In previous comparisons with laboratory glucose measurements, the HemoCue Glucose 201 system has been found to be accurate [27,28]. When HC210RT was compared to accredited hospital laboratory methods in subjects with coronary artery disease in a European survey, the Bland-Altman plot showed small differences and, in contrast to our findings, a tendency of higher glucose measurements for HC201RT than for hospital laboratory measurements [28].…”
Section: Discussioncontrasting
confidence: 74%
“…In previous comparisons with laboratory glucose measurements, the HemoCue Glucose 201 system has been found to be accurate [27,28]. When HC210RT was compared to accredited hospital laboratory methods in subjects with coronary artery disease in a European survey, the Bland-Altman plot showed small differences and, in contrast to our findings, a tendency of higher glucose measurements for HC201RT than for hospital laboratory measurements [28]. The −1.8% bias noted for the HC201RT instrument in the present study is close to the 2.2% limit for acceptable bias according to international guidelines [15].…”
Section: Discussionmentioning
confidence: 98%
“…These concerns have all been addressed. Shahim et al (30) concluded that the agreement between glucose measurements made by the point-ofcare HemoCue Glucose 201 RT System, used in EAV, and local hospital laboratories is excellent. The application of an accurate, user-friendly point-of-care technology for glucose measurement saves time, reduces costs, and eliminates at least some of the preanalytical errors, in particular those related to delayed sample handling, while providing almost instantaneous information on the patient's glycemic state.…”
Section: Discussionmentioning
confidence: 99%
“…All patients without known diabetes were offered an Oral Glucose Tolerance test (OGTT; 75 g glucose in 200 mL water). Plasma glucose (PG) was analysed locally in the fasting state (FPG) and 2 h after the glucose load (2 h-PG) with a photometric point-of-care technique (Glucose 201 + (EAIV) or Glucose 201RT (EAV); HemoCue, Ängelholm, Sweden) [23]. Since the HemoCue technique is cholesterol-sensitive, glucose values were corrected for cholesterol according to the formula: HemoCue glucose + 0.15 x (total cholesterol − 5).…”
Section: Methodsmentioning
confidence: 99%